Pengaruh Penggunaan Iklan Berbasis User Generated Content (UGC) di Tiktok terhadap Minat Pembelian - Siregar, Michael Eason Doli; Junaidi, Ahmad (Kiwari, 2025)
Advertising is a dynamic industry, involving indirect communication of product advantages and benefits. Digital marketing is experiencing rapid growth, with 137% of digital marketing reaching 72% of consumers. This research aims to expand understanding in the advertising concentration, specifically regarding the use of User-Generated Content (UGC) to increase sales and product exposure. Using a quantitative approach, data was obtained through a questionnaire from TikTok users interested in skincare products. Validity and reliability tests showed all items were valid and reliable, with a Cronbach's Alpha value of 0.960. The regression test results show that UGC has a significant influence on consumer purchase intention by 50.6% (R² = 0.506). Partial tests confirmed the significant effect of UGC on the dependent variable, with a t value of 10.021> t table. This study demonstrates the effectiveness of UGC on TikTok in creating visual appeal, increasing audience engagement, and building review credibility. This study contributes to the development of digital-based marketing strategies, particularly in the context of skincare products such as Avoskin, and underscores the importance of user participation in optimizing advertising campaigns in the digital age. Periklanan adalah industri yang dinamis, melibatkan komunikasi tidak langsung mengenai kelebihan dan manfaat produk. Pemasaran digital mengalami pertumbuhan pesat, dengan 137% dari pemasaran digital menjangkau 72% konsumen. Penelitian ini bertujuan untuk memperluas pemahaman dalam konsentrasi periklanan, khususnya mengenai penggunaan User-Generated Content (UGC) untuk meningkatkan penjualan dan eksposur produk. Dengan pendekatan kuantitatif, data diperoleh melalui kuesioner dari pengguna TikTok yang tertarik pada produk skincare. Uji validitas dan reliabilitas menunjukkan semua item valid dan reliabel, dengan nilai Cronbach's Alpha sebesar 0,960. Hasil uji regresi menunjukkan bahwa UGC memberikan pengaruh signifikan terhadap minat beli konsumen sebesar 50,6% (R² = 0,506). Uji parsial menegaskan pengaruh signifikan UGC terhadap variabel dependen, dengan nilai t hitung 10,021 > t tabel. Penelitian ini menunjukkan efektivitas UGC di TikTok dalam menciptakan daya tarik visual, meningkatkan keterlibatan audiens, dan membangun kredibilitas ulasan. Studi ini memberikan kontribusi bagi pengembangan strategi pemasaran berbasis digital, khususnya dalam konteks produk skincare seperti Avoskin, dan menggarisbawahi pentingnya partisipasi pengguna dalam mengoptimalkan kampanye iklan di era digital.